Impaired glucose metabolism among those with and without diagnosed diabetes and mortality: a cohort study using Health Survey for England data. - Vanessa L Z Gordon-Dseagu; Jennifer S Mindell; Andrew Steptoe; Alison Moody; Jane Wardle; Panayotes Demakakos; Nicola J Shelton (PLoS ONE)
Background The extent that controlled diabetes impacts upon mortality, compared with uncontrolled diabetes, and how pre-diabetes alters mortality risk remain issues requiring clarification. Methods We carried out a cohort study of 22,106 Health Survey for England participants with a HbA1C measurement linked with UK mortality records. We estimated hazard ratios (HRs) of all-cause, cancer and cardiovascular disease (CVD) mortality and 95% confidence intervals (CI) using Cox regression. Results Average follow-up time was seven years and there were 1,509 deaths within the sample. Compared with the non-diabetic and normoglycaemic group (HbA1C <5.7% [<39 mmol/mol] and did not indicate diabetes), undiagnosed diabetes (HbA1C ≥6.5% [≥48 mmol/mol] and did not indicate diabetes) inferred an increased risk of mortality for all-causes (HR 1.40, 1.09-1.80) and CVD (1.99, 1.35-2.94), as did uncontrolled diabetes (diagnosed diabetes and HbA1C ≥6.5% [≥48 mmol/mol]) and diabetes with moderately raised HbA1C (diagnosed diabetes and HbA1C 5.7-<6.5% [39-<48 mmol/mol]). Those with controlled diabetes (diagnosed diabetes and HbA<5.7% [<39 mmol/mol]) had an increased HR in relation to mortality from CVD only. Pre-diabetes (those who did not indicate diagnosed diabetes and HbA1C 5.7-<6.5% [39-<48 mmol/mol]) was not associated with increased mortality, and raised HbA1C did not appear to have a statistically significant impact upon cancer mortality. Adjustment for BMI and socioeconomic status had a limited impact upon our results. We also found women had a higher all-cause and CVD mortality risk compared with men. Conclusions We found higher rates of all-cause and CVD mortality among those with raised HbA1C, but not for those with pre-diabetes, compared with those without diabetes. This excess differed by sex and diabetes status. The large number of deaths from cancer and CVD globally suggests that controlling blood glucose levels and policies to prevent hyperglycaemia should be considered public health priorities.